2011
DOI: 10.1038/ejcn.2011.174
|View full text |Cite
|
Sign up to set email alerts
|

Infant diet and subcutaneous fat mass in early childhood: The Generation R Study

Abstract: Background/Objectives: Breastfeeding has a protective effect on childhood obesity, but the influences on body composition in early childhood are not known. The objective of this study is to assess whether the duration and exclusiveness of breastfeeding, and the timing of introduction of solid foods are associated with the subcutaneous fat mass in early childhood. Subjects/Methods: This study was embedded in a population-based prospective cohort study among 779 children. Peripheral (biceps, triceps) and central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 40 publications
(52 reference statements)
1
18
2
2
Order By: Relevance
“…Our data showed higher body fat at an age of > 12 months in never breastfed children and are in line with previous studies showing in children who were not exclusively breastfed higher central fat mass at the age of 24 months. 24 However, our current report revealed no association between breastfeeding duration and body composition during the first 2 years of life. Our findings are partially consistent with Durmus et al, 24 who reported that shorter breastfeeding was associated with higher fat mass at the age of 6 months, but not at the age of 24 months.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Our data showed higher body fat at an age of > 12 months in never breastfed children and are in line with previous studies showing in children who were not exclusively breastfed higher central fat mass at the age of 24 months. 24 However, our current report revealed no association between breastfeeding duration and body composition during the first 2 years of life. Our findings are partially consistent with Durmus et al, 24 who reported that shorter breastfeeding was associated with higher fat mass at the age of 6 months, but not at the age of 24 months.…”
Section: Discussioncontrasting
confidence: 48%
“…24 However, our current report revealed no association between breastfeeding duration and body composition during the first 2 years of life. Our findings are partially consistent with Durmus et al, 24 who reported that shorter breastfeeding was associated with higher fat mass at the age of 6 months, but not at the age of 24 months.…”
Section: Discussioncontrasting
confidence: 48%
“…Of the 17 studies (includes Huh et al 29 ) that showed no association, [19][20][21]23,24,29,[34][35][36][37][38][39][40][41][42][43][44] two included only breastfed infants, 29,37 two included exclusively formula-fed infants 21,43 and four 35,36,39,44 are quality studies with large (>1000) representative contemporary cohorts and robust multivariable models. The only RCT 21 showed no difference in anthropometrics or body composition at 12 months between infants introduced to solids at 3-4 versus 6 months of age.…”
Section: Resultsmentioning
confidence: 99%
“…In general, these studies showed that greater adiposity in infancy and childhood was associated to female sex 4,5,6,7,8,9 , white skin color 7,9,10,11 , higher birth 4,12 and current weight 12,13,14 , higher pre-gestational maternal 4,7,15 and paternal body mass index 14,16 , maternal smoking in pregnancy 15,16,17 , and shorter duration of breastfeeding 6,18 , whereas the role of socioeconomic conditions is controversial at the literature 7,14,16,19,20 . No studies were found in countries such as Brazil, where epidemiological and nutritional transitions are still playing out 21,22 , leaving a gap with regard to the effect of these transitions on body composition in childhood.…”
Section: Introductionmentioning
confidence: 99%